A feed forward loop enforces YAP/TAZ signaling during tumorigenesis - Mandeep K. Gill (Nature Portfolio, 2018)
The Hippo pathway is frequently dysregulated in cancer. Here, the authors identify NUAK2 as negative regulator of the Hippo pathway from a siRNA kinome screen and show that NUAK2 promotes YAP/TAZ nuclear localisation while NUAK2 is a transcriptional target of YAP/TAZ, thus providing a feed forward loop to promote tumorigenesis.